Genome-wide identification and expression profiles of NAC transcription factors in Poncirus trifoliata reveal their potential roles in cold tolerance - Tian Fang; Yue Wang; Haowei Chen; Jing Qu; Peng Xiao; Yilei Wang; Xin Jiang; Chunlong Li; Ji-Hong Liu (BMC Plant Biology)
Abstract Background Citrus, a globally vital economic crop, faces severe challenges due to extreme climatic conditions and diseases/pests attack. Poncirus trifoliata is closely related to citrus and shows unique cold tolerance, making it a crucial material for unraveling genes involved in cold tolerance. NAC (NAM, ATAF1/2, CUC2) transcription factors play important roles in plant growth, development, and stress responses. However, their evolution patterns and gene functions in citrus remain poorly studied. This study aims to elucidate the genomic characteristics and evolution of the NAC genes in P. trifoliata, and to analyze their expression patterns and conduct functional validation under cold stress. Results Genome-wide analysis identified 135 PtrNAC genes in P. trifoliata with non-random chromosomal distribution, including 20 gene clusters. 57.78% of the NAC genes are located in the chromosomes 3, 4 and 5. Gene duplication analysis revealed that proximal and tandem duplications as primary expansion mechanisms, with tandem repeats specifically driving gene expansion in citrus lineages (subfamilies IV, V, and VII). Collinearity analysis showed that 24.44% of the PtrNAC genes were retained in homologous regions, and Ka/Ks ratio analysis further confirmed that purifying selection dominated their evolutionary process. Transcriptome landscapes revealed that Pt5g024390 (PtrNAC2) was induced to the greatest degree under the cold stress. Meanwhile, expression level of PtrNAC2 in tetraploid was more than two folds higher compared to diploid counterpart in the presence of cold stress. Virus-induced gene silencing of PtrNAC2 led to significantly enhanced cold tolerance, implying that it plays a negative role in regulation of cold tolerance. Conclusion This study systematically elucidated the global distribution and evolutionary patterns of NAC genes in P. trifoliata. In addition, the NAC gene exhibit adaptive expansion driven by tandem duplications. The identification of PtrNAC2, a negative regulator of cold tolerance in P. trifoliata, provides valuable insights into unravelling potential candidates for engineering cold tolerance in citrus.